The Public Statutes of the Commonwealth of Massachusetts 381 (1882) - (:unkn) unknown (My University, 1882)
§§ 29-31: Gunpowder manufactured in this commonwealth shall be put into strong and tight casks containing twenty-five pounds, fifty pounds, or one hundred pounds each, or well secured in copper, tin, or brass canisters holding not more than five pounds each, and closely covered with copper, brass, or tin covers. § 30. Each cask containing gunpowder manufactured within this commonwealth, or brought into the same by land or by water and landed, shall be marked on the head with black paint in legible characters with the word gunpowder, the name of the manufacturer, the weight of the cask, and the year in which the powder was manufactured; and each canister of gunpowder shall be marked with the word gunpowder. § 31. Whoever knowingly marks a cask of gunpowder with the name of any person other than the manufacturer of the same, or changes gunpowder from a cask marked with the name of one manufacturer into a cask marked with the name of another manufacturer, shall for each offence forfeit a sum not exceeding twenty dollars.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER